Arterial Hypertension and Diabetes Mellitus in the Pathogenesis of Primary Open-Angle Glaucoma: A Balkan Perspective (Ukrainian Journal of Ophthalmology, 2025)
Purpose. To identify specific risk factors and protective factors to inform tailored screening and management strategies for high-risk individuals.Methods. This case-control study included a total of 800 eyes from 400 individuals, comprising 200 pairs of eyes diagnosed with primary open-angle glaucoma (POAG) and 200 glaucoma-free (the control group). Data were collected through structured questionnaires and comprehensive ophthalmologic examinations. Statistical analyses were performed to assess the association between POAG and systemic conditions such as diabetes and hypertension, as well as various sociodemographic factors.Results. Systolic arterial hypertension was identified as a risk factor (p
Keywords: primary open angle glaucoma; risk factors; diabetes; arterial hypertension; glaucoma screening